The basic definitions of Artificial Intelligence operating system: "AI-Consciousness”, "AI-Time”, "AI-Know/not_know” and "AI-Memory” concepts - Kornieiev, S. (Штучний інтелект, 2018)
The article concerns the concept of “Artificial General Intelligence” (AGI) and in particular the issue of its basic definitions. In this article the following definitions had been proposed: “AI-consciousness”, “AI-Time”, “AI-Understanding” and “AI-memory”. The goal of the definitions is to be used in the modelling of AI-OS (Artificial Intelligence Operating System). As seen together the set of formulated definitions allow to model AI-OS for productive use. A distinctive feature of presented definitions is that they, if compared with known ones, allow the simulation and design of AI-OS using known methods and approaches.